African swine fever virus MGF360-4L protein attenuates type I interferon response by suppressing the phosphorylation of IRF3 - Wang, Zhen; He, Yuheng; Huang, Ying; Zhai, Wenzhu; Tao, Chunhao; Chu, Yuanyuan; Pang, Zhongbao; Zhu, Hongfei; Zhao, Peng; Jia, Hong (Frontiers in Immunology, 2024)
African swine fever (ASF) is a highly contagious and lethal disease of swine caused by African swine fever virus (ASFV), and the mortality rate caused by virulent stains can approach 100%. Many ASFV viral proteins suppress the interferon production to evade the host's innate immune responses. However, whether ASFV MGF360-4L could inhibit type I interferon (IFN-I) signaling pathway and the underlying molecular mechanisms remain unknown. Our study, indicated that ASFV MGF360-4L could negatively regulates the cGAS-STING mediated IFN-I signaling pathway. Overexpressing ASFV MGF360-4L could inhibit the cGAS/STING signaling pathway by inhibiting the interferon-β promoter activity, which was induced by cGAS/STING, TBK1, and IRF3-5D, and further reduced the transcriptional levels of ISG15, ISG54, ISG56, STAT1, STAT2, and TYK2. Confocal microscopy and immunoprecipitation revealed that MGF360-4L co-localized and interacted with IRF3, and WB revealed that ASFV MGF360-4L suppressed the phosphorylation of IRF3. 4L-F2 (75-162 aa) and 4L-F3 (146-387 aa) were the crucial immunosuppressive domains and sites. Altogether, our study reveals ASFV MGF360-4L inhibited cGAS-STING mediated IFN-I signaling pathways, which provides insights into an evasion strategy of ASFV involving in host's innate immune responses.